The Power of Perspective. Discrimination Against Men - Virág Véber (Elpis)
Despite their conscious beliefs, values, and attitudes, people often have prejudices that influence their behaviour — such as gender bias. In my study, I point out that not only women are affected by gender bias, but men are as well, by the binary gender perspective: an important aspect of eliminating discrimination against women is that we need to address male bias as well. In my paper, I rely primarily on the concept of stereotype threat and Stacey Goguen’s thoughts. I point out that by prescribing hostile and benevolent sexism to traditional roles for both men and women, both will be problematic in the fight against discrimination. I examine stereotypes about men and their implications for men’s self-image as well as gender in general.